PENGARUH LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN (SIZE) TERHADAP STRUKTUR MODAL DENGAN TINGKAT SUKU BUNGA SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR YANG TERDAPAT DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2018 - Cynthia Dorkas; Jonnardi; MF Djeni Indrajati (Fakultas Ekonomi Universitas Tarumanagara, 2022)
The purpose of this study was to examine the effect of Liquidity, Profitability. Size to Capital Structure. The method used in this research is simple random sampling. The data used in this study was simple random sampling. Simple random sampling is done by taking a sample from the population not based on a certain criteria. manufacturing sector company on the Indonesia Stock Exchange. The results of the data collection were processed using EVIEWS. The results of this study indicate that liquidity, profitability, company size have a significant effect partially on capital structure. Profitability and Interest Rate do not have a significant effect on Company Value. Liquidity and Size have a significant effect on Company Value simultaneously.